국내 밈 주요 유형 연구 - 홍소람; Soram Hong (Chŏngbo Kwalli Hakhoechi, 2025)
Memes are effective information resources for literacy education required in a digital technology-based information environment. The purpose of this study is to derive the main meme types in South Korea according to sociocultural context and to provide basic data for literacy education. To this end, two research questions were addressed. First, what are the different ways to classify memes? Second, how are South Korean memes categorized? This study derived the classification types of memes through a literature review and analyzed 830 South Korean memes from Namuwiki, a South Korean subcultural wiki site. The analysis methods used were frequency analysis, chi-squared test, and network analysis. The results are as follows. First, memes are classified by medium, origin, unethical label, subject, and time period of occurrence. Second, South Korean memes are categorized into 4 main types: Language memes produced through everyday communication in online communities and social media in the 2010s; Complex memes for a play culture based on new media contents in the 2020s; Visual memes of South Korean internet culture in the early 2020s; Parody memes of legacy media. 밈은 디지털 기술 기반의 정보환경에서 요구되는 다양한 유형의 리터러시 교육을 위한 효과적인 정보자원이다. 이 연구의 목적은 우리나라의 밈의 주요 유형을 사회문화적 맥락에 근거하여 도출해냄으로써 리터러시 교육의 기초자료를 마련하는 것이다. 이를 위하여 두 가지 연구질문을 소명하였다. 첫째, 밈의 분류 방식은 어떤 것들이 있는가? 둘째, 우리나라의 밈은 어떻게 유형화되는가? 이 연구는 문헌연구를 통해 밈의 분류 종류를 도출하고, 국내 서브컬쳐 위키 사이트인 나무위키에 등재된 우리나라의 밈 830개를 분석하였다. 분석 방법으로는 빈도분석, 교차분석, 네트워크 분석을 사용하였다. 그 결과는 다음과 같다. 첫째, 밈은 매체, 유래, 비윤리 라벨, 주제, 발생연대로 분류된다. 둘째, 우리나라의 밈은 다음과 같이 4가지 주요 유형으로 나눠진다: 2010년대의 커뮤니티/SNS에서 일상적 소통 과정 중에 강화된 언어 밈; 2020년대 뉴미디어 콘텐츠를 토대로 한 놀이문화적 복합 밈; 2000년대 우리나라 인터넷 문화 초기 등장했던 시각 밈; 레거시 미디어 기반의 패러디 밈.